Ethanol abolishes vigilance-dependent astroglia network activation in mice by inhibiting norepinephrine release - Liang Ye (Nature Portfolio, 2020)
The effects of norepinephrine on sensory processing in cortical networks are altered by recreational drugs like ethanol. The authors show that ethanol suppresses the activation of astrocytes by inhibiting norepinephrine release which may contribute to the cognitive effects of alcohol intoxication.